Looking Back on Contributions in the Field of Atmospheric Corrosion Offered by the MICAT Ibero-American Testing Network. (7th March 2012) - Morcillo, M.; Chico, B.; de la Fuente, D.; Simancas, J.
Abstract : The Ibero-American Map of Atmospheric Corrosiveness (MICAT) project was set up in 1988 sponsored by the International Ibero-American programme "Science and Technology for Development (CYTED)" and ended in 1994 after six years of activities. Fourteen countries were involved in this project: Argentina, Brazil, Chile, Colombia, Costa Rica, Cuba, Ecuador, Mexico, Panama, Peru, Portugal, Spain, Uruguay, and Venezuela. Research was conducted both at laboratories and in a network of 75 atmospheric exposure test sites throughout the Ibero-American region, thus considering a broad spectrum of climatological and pollution conditions. Although with its own peculiarities, the project basically followed the outline of the ISOCORRAG and ICP/UNECE projects, with the aim of a desirable link between the three projects. This paper summarizes the results obtained in the MICAT project for mild steel, zinc, copper, and aluminum specimens exposed for one year in different rural, urban, and marine atmospheres in the Ibero-American region. Complementary morphological and chemical studies were carried out using scanning electron microscopy (SEM) coupled with energy dispersive spectrometry (EDS), X-ray diffraction (XRD), and fourier transform infrared Spectroscopy (FTIR) techniques, in order to correlate climatic and atmospheric conditions and properties of the corrosion products.